A SYSTEMATIC EXAMINATION OF THE MUCOUS MEMBRANE OF THE MOUTH (ORAL MUCOUS MEMBRANE) – THE WAY TO PREVENT MALIGNANCIES - I. K. Lutskaya; S. V. Latysheva (Український стоматологічний альманах, 2017)
The article presents information on the liability of the dentist to reduce the risk of pathological processes development, including malignant neoplasms in the oral cavity. A thorough inspection of the oral mucous membrane, in accordance with WHO recommendations provides a systematic survey of all parts of the oral cavity and surrounding tissues. This tactic can significantly reduce the risk of pathological lesions development in the oral cavity, to prevent malignant transformation or provide early diagnosis.